ASSESSMENT AND IDENTIFICATION OF BACTERIA IN SAGU LEMPENG SOLD IN AMBON CITY, INDONESIA - Taher, Dilya Maghfirah; Yunita, Melda; Taihuttu, Yuniasih Mulyani Jubeliene; Azizah, Siti Nur (Folia Medica Indonesiana, 2025)
Maluku Province in Indonesia is known for its diverse traditional foods, including sagu lempeng, which is widely consumed across different social groups. However, poor hygiene during its preparation, packaging, and sale in traditional markets can serve as a medium for microbial contamination, posing potential health risks. In Ambon City, the capital of Maluku, no research had been conducted concerning the total plate count (TPC) analysis and identification of food-contaminating bacteria in sagu lempeng, which are crucial for ensuring its microbiological safety. Therefore, this study aimed to assess the microbiological quality of sagu lempeng according to Indonesian National Standards (INS 7388:2009) and to identify any presence of food-contaminating bacteria. This research employed a quantitative descriptive methodology with a true experimental laboratory approach. The samples used were sagu lempeng collected from three traditional markets in Ambon, Indonesia. The TPC analysis was conducted to estimate the number of bacterial colonies per gram of samples, while Gram staining and biochemical testing were carried out for macroscopic and microscopic bacterial identification. The results showed that the highest TPC was found in sagu lempeng from Waiheru Market at 8.1 × 105 CFU/g, while the lowest was from Mardika Market at 5.95 × 103 CFU/g. The identified bacteria included Klebsiella pneumoniae ssp. and Staphylococcus arlettae. Although bacterial contamination was detected, the TPC of sagu lempeng from all sampled markets remained under the maximum allowable limit set by Indonesian National Standards (1 × 106 CFU/g). In conclusion, sagu lempeng sold in traditional markets around Ambon complies with microbiological safety standards and is considered safe for consumption.